Allylic peroxidations with bis(2-pyridylimino)isoindolato-cobalt and -iron complexes: dedicated to Professor Michael Veith on the occasion of his 60th birthday - Meder, Markus B.; Siggelkow, Bettina A.; Gade, Lutz H. (Zeitschrift für anorganische und allgemeine Chemie, 2004)
Several novel substituted bis(2-pyridylimino)isoindolato (BPI) cobalt(II) and iron(II) complexes [M(BPI)(OAc)(H2O)] (M = Co: 1 - 6, Fe: 7) have been synthesized by reaction of bis(2-pyridylimino)isoindole derivatives with the corresponding metal(II) acetates. Reaction of 1-6 with 1.5 - 2 molar equivalents of t-BuOOH gave the corresponding alkylperoxocobalt(III) complexes [Co(BPI)(OAc)(OOtBu)] (10 - 15). Using an aqueous solution of t-BuOOH (70 %), cyclohexene was selectively catalytically oxidized to the dialkylperoxide cyclohex-2-ene-1-t-butylperoxide.